2015
DOI: 10.1016/j.leaqua.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing leadership perceptions as attitudes: Using attitude theory to further understand the leadership process

Abstract: Leadership is one of the most examined factors in relation to understanding employee wellbeing and performance. While there are disparate approaches to studying leadership, they share a common assumption that perceptions of a leader's behavior determine reactions to the leader.The concept of leadership perception is poorly understood in most theoretical approaches. To address this, we propose that there are many benefits from examining leadership perceptions as an attitude towards the leader. In this review, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 193 publications
(189 reference statements)
1
33
0
Order By: Relevance
“…The recent proliferation of "positive" forms of leadership (i.e., servant, authentic, empowering, and ethical leadership) has served to exacerbate the problem. The uniform pattern of small-moderate positive correlations between positive leader styles and creativity/innovation, regardless of the nature of the style, suggests that we might be measuring overall attitudes towards leaders rather than actual behaviors (Baumeister et al, 2007;Lee, Martin, Thomas, Guillaume, & Maio, 2015). Future research needs to address the lack of theoretical clarity by focusing on the distinctive elements of leadership approaches and their relative and incremental effects.…”
Section: Leadership: Main Effectsmentioning
confidence: 99%
“…The recent proliferation of "positive" forms of leadership (i.e., servant, authentic, empowering, and ethical leadership) has served to exacerbate the problem. The uniform pattern of small-moderate positive correlations between positive leader styles and creativity/innovation, regardless of the nature of the style, suggests that we might be measuring overall attitudes towards leaders rather than actual behaviors (Baumeister et al, 2007;Lee, Martin, Thomas, Guillaume, & Maio, 2015). Future research needs to address the lack of theoretical clarity by focusing on the distinctive elements of leadership approaches and their relative and incremental effects.…”
Section: Leadership: Main Effectsmentioning
confidence: 99%
“…Leadership has a significant effect on attitudes, behaviors, and various levels of performance [12,13], including the sustainability of organizations [14]. Recent studies on leadership have discussed sustainable leadership, which focuses on a leaders' attitude and behavior towards connecting organizations to innovation and systematic change as a response to the business environment, society, business ethics, and corporate responsibility [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Most publications identified from top-tier publications such as Leadership Quarterly, Journal of Management, Organizational Science, and others related to leadership have acknowledged the role of leadership in influencing the organization (Dinh et al, 2014). Lee, Martin, Thomas, Guillaume, and Maio (2015) concluded that social identity of the workgroup affected a holistic view of a team, including both leader strategies and follower attitudes. A review of leadership training programs yielded no evidence of leader exposure to these modern concepts.…”
Section: Leadershipmentioning
confidence: 99%
“…(Gaudet & Tremblay, 2017). Huettermann, Doering, and Boerner (2014) Contemporary researchers continue to demonstrate the need to go beyond leadership traits to understand leadership, and opportunities to improve team performance (Lee, Martin, Thomas, Guillaume, & Maio, 2015;Asrar-ul-Haq & Kuchinke, 2016). Lee et al (2015) noted that follower perceptions require a multifaceted investigation of leadership to understand how leadership strategies affect the perceptions of the followers.…”
Section: Leader-member Exchange Theorymentioning
confidence: 99%
See 1 more Smart Citation